2016
DOI: 10.1080/00396265.2016.1173329
|View full text |Cite
|
Sign up to set email alerts
|

Weighted coordinate transformation formulated by standard least-squares theory

Abstract: This paper presents a universal model of weighted coordinate transformation, i.e. transformation considering the errors of coordinates in both coordinate systems. It is intrinsically one of the typical examples of 'error-in-variables' (EIV) models. The proposed method of LS theory application on weighted coordinate transformation does not impose any constraints on the form of functional relationship among stochastic variables. Since the basic idea is to generalise Gauss-Markov model (GMM) by introduction of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In that case, [9] has shown that the total least-squares solution can be obtained easily from a rigorous evaluation of the Gauss-Helmert model. A good discussion about total leastsquares algorithms can be seen in [9,10,18]. Different from the approaches mentioned so far, in the following sections, we present an alternative method based on the Monte Carlo method.…”
Section: The Gauss-markov Model In the Context Of Coordinate Transformationmentioning
confidence: 99%
“…In that case, [9] has shown that the total least-squares solution can be obtained easily from a rigorous evaluation of the Gauss-Helmert model. A good discussion about total leastsquares algorithms can be seen in [9,10,18]. Different from the approaches mentioned so far, in the following sections, we present an alternative method based on the Monte Carlo method.…”
Section: The Gauss-markov Model In the Context Of Coordinate Transformationmentioning
confidence: 99%
“…So far, a large number of algorithms of three-dimensional coordinate transformation have been presented (cf., e.g., Aydin et al 2018;Grafarend and Awange 2003;Kanatani and Niitsuma 2012;Kurt 2018;Ligas and Prochniewicz 2019;Mahboub 2016;Marx 2017;Mercan et al 2018;Mihajlović and Cvijetinović 2017;Păun et al 2017;Shen et al 2006;Uygur et al 2020;Walker et al 1991;Wang et al 2014;Zeng 2015;Yi 2010, 2011;Zeng et al 2016Zeng et al , 2018Zeng et al , 2019. They can be classified into iterative algorithm or analytical algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…e.g. Chen et al (2004), El-Habiby et al (2009, Neitzel (2010), Yi (2011), Fang (2015), Mahboub (2016), Zeng et al (2016), Mihajlović and Cvijetinović (2017), Kurt (2018), Mercan et al (2018), Zeng et al (2019), Qin et al (2020), Ioannidou and Pantazis (2020). They require initial values of transformation parameters and linearization and iterative computation.…”
Section: Introductionmentioning
confidence: 99%